Optimized fast fourier transform architecture using instruction set architecture extension in low-end digital signal controller - Salim, Sani Irwan (2018)
Smart microgrids have emerged as a viable solution in case of emergency situations occurred at the main electricity grid. The main concern of a smart microgrid is the degradation of the power quality caused by harmonic distortion originated from the non-linear equipment. With the rapid development of power electronic technology, the increased of harmonic-producing loads in the smart microgrids necessitating a new digital signal controller architecture for the harmonic measurement system. While the current system configurations are directed towards the 32-bit architecture, it shows higher requirements in area footprint and multi-core setup. This thesis presents the design of a low-end digital signal controller architecture using instruction set architecture (ISA) extension for the implementation of the harmonic measurement system in a smart microgrid. A new architecture, called UTeMRISC, is developed from the baseline 8-bit microcontroller with the capability to perform signal processing applications such as Fast Fourier Transform (FFT). The architecture is improved using the Application-Specific Instruction Set Processor (ASIP) approach by extending the instruction set architecture to 16-bit length. Instruction set customization is implemented to enable the execution of computationally intensive tasks. The entire architecture is described in Verilog Hardware Description Language (HDL) and implemented on the Virtex-6 FPGA board. From the test programs, UTeMRISC has demonstrated faster execution times and higher maximum operating frequency while not significantly increased the core’s resource utilization. Compared to the initial processor architecture, the support of extended ISA has increased the UTeMRISC core by 21.8% but at the same time allows to execute Fast Fourier Transform algorithm up to 5× faster. The combine effort of ISA extension and optimized instruction set generation results in up to 1 Mega sample per second, which translated to 66.8% increase of data throughput in the FFT algorithm when compared to a 32-bit architecture. This research proves that with comprehensive ASIP methodology and ISA extension, a low-end digital signal controller architecture is feasible and effective to be implemented in a harmonic measurement system for a smart microgrid.